Alua Jo Patuik Simarantang Karang Manih dalam Bingkai Proses Kreatif Efyuhardi - Fani Dila Sari (Universitas Gadjah Mada, 2019)
Intellectual beauty is a wonderful thought based on science. The beauty in the sense of a purely aesthetic concerns aesthetic experience of a person in relation to everything dicerapnya. Efyuhardi traditions of knowledge as the son of Pariaman area, as well as the knowledge acquired through the theater Theater Arts education makes work interesting Manih Simarantang Reefs for review of the creative process. Efyuhardi implement cultural creativity in the form of Pariaman to Simarantang identified as Tuo Randai. Efyuhardi creative acts of the creation of the Simarantang Karang Manih shelter on aesthetics Minangkabau is Alua jo Patuik. Keywords: Simarantang Karang Manih, Efyuhardi, and Alua jo Patuik